2010
DOI: 10.1007/s00122-010-1400-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular marker survey and expression analyses of the rice submergence-tolerance gene SUB1A

Abstract: The major rice quantitative-trait locus Submergence 1 (Sub1) confers tolerance of submergence for about 2 weeks. To identify novel sources of tolerance, we have conducted a germplasm survey with allele-specific markers targeting SUB1A and SUB1C, two of the three transcription-factor genes within the Sub1 locus. The objective was to identify tolerant genotypes without the SUB1A gene or with the intolerant SUB1A-2 allele. The survey revealed that all tolerant genotypes possessed the tolerant Sub1 haplotype (SUB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 22 publications
10
84
0
Order By: Relevance
“…These two alleles encode proteins that only differ at a single amino acid, Ser-186 in SUB1A-1 and Pro-186 in SUB1A-2, a putative mitogen-activated protein kinase (MPK) phosphorylation site in SUB1A-1 . To further assess the determination of submergence tolerance by SUB1A, Singh et al (2010) evaluated SUB1A genotype and submergence tolerance in 76 rice accessions from a variety of geographic locations. Although tolerance was highly correlated with strong up-regulation of SUB1A-1 mRNA during submergence, there was an imperfect association between tolerance and SUB1A-1.…”
Section: Quiescence Strategy Of Submergence-tolerant Ricementioning
confidence: 99%
“…These two alleles encode proteins that only differ at a single amino acid, Ser-186 in SUB1A-1 and Pro-186 in SUB1A-2, a putative mitogen-activated protein kinase (MPK) phosphorylation site in SUB1A-1 . To further assess the determination of submergence tolerance by SUB1A, Singh et al (2010) evaluated SUB1A genotype and submergence tolerance in 76 rice accessions from a variety of geographic locations. Although tolerance was highly correlated with strong up-regulation of SUB1A-1 mRNA during submergence, there was an imperfect association between tolerance and SUB1A-1.…”
Section: Quiescence Strategy Of Submergence-tolerant Ricementioning
confidence: 99%
“…This result was similar with the finding of Septiningsih et al (2012), where the SUB1A gene in the variety Madabaru, a moderately tolerant variety, was highly expressed under submergence, even though this variety had the 'susceptible' allele SUB1A-2. Likewise, Singh et al (2010) had reported that the susceptible SUB1A-2 allele identified in the variety James Wee was highly expressed under submergence, despite the fact that this variety was moderately tolerant to submergence. Therefore, for a diversity study, in addition to the use of SUB1 DNA markers it is imperative to check the expression of SUB1A to confirm whether SUB1 indeed plays a role in contributing to submergence tolerance.…”
Section: +mentioning
confidence: 99%
“…An extensive analysis of diverse rice accessions with different SUB1 haplotype showed that submergence tolerance is associated with variable levels of SUB1A transcript in internodes and nodes at the heading stage (Singh et al 2010). In Nipponbare transgenics expressing the GUS reporter gene under the control of the native SUB1A promoter, GUS activity was specifically induced by submergence in regions of leaves associated with growth, i.e., the leaf base and leaf collar, suggesting that SUB1A might act on the processes of cell division and/or cell elongation in leaves under submergence.…”
Section: Mapping and Molecular Characterization Of Sub1mentioning
confidence: 99%